Демографічні перспективи України - Дрозач, Максим Іванович (My University, 2023)
В статті розглядаються демографічні перспективи України в контексті існуючої ситуації та прогнозів її розвитку. Автори статті аналізують імовірність виникнення демографічної кризи в Україні та її глибину внаслідок впливу низки негативних факторів. Для досягнення поставленої мети виконані наступні завдання: проаналізовано поточну ситуацію в Україні, зумовлену об’єктивними та суб’єктивними факторами, а також запропоновано можливості для покращення демографічної ситуації в Україні в середньота довгостроковій перспективі. The article discusses the demographic prospects of Ukraine in the context of the current situation and forecasts of its development. The authors of the article analyze the probability of the demographic crisis in Ukraine and its depth due to the influence of several negative factors. To achieve this goal, the following tasks were performed: the current situation in Ukraine, due to objective and subjective factors, was analyzed, and opportunities for improving the demographic situation in Ukraine in the medium and long term were proposed. After gaining independence, the demographic situation in Ukraine has become more complicated: a decline in the birth rate, an aging population, a deterioration in the health of the nation, economic instability in the country, as well as migration processes (more people leave Ukraine than return).
Keywords: війна; war; ринок праці; labor market; демографічна ситуація; demographic situation